Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Associations between metabolic dysfunction–associated steatotic liver disease and physical and mental health–related quality of life in older adults - Marzieh Nasr Azadani; Mojtaba Lotfaliany; Najmeh Davoodian; Michael Berk; Robyn L. Woods; Joanne Ryan; John J. McNeil; Julie A. Pasco; Nigel Stocks; Stuart K. Roberts; William Kemp; Ammar Majeed; et al. (GeroScience, 2026)

Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Rat and human primary proximal tubule epithelial cells allow for cross-species comparisons of drug-induced nephrotoxicity in vitro - Stan A. Zuidervaart; Bobin G. Abraham; Paul A. Fitzpatrick; Anna-Karin Sjögren; Catherine C. Bell (Archives of Toxicology, 2026)

Sensory profile and drivers of liking of grass-fed and total mixed ration butters - Lauren McGuinness; Mark Timlin; Sean A. Hogan; Tom F. O'Callaghan; John P. Murphy; Deirdre Hennessy; Michael O'Donovan; Ellen Fitzpatrick; Kieran McCarthy; E. Dolores O'Riordan; Andre Brodkorb; Emma L. Feeney (Food Quality and Preference, 2026)

Release of β-casomorphin-7 in A1/A1 and A2/A2 dairy systems: Insights from simulated semi-dynamic gastrointestinal digestion - Davor Daniloski; Noel A. McCarthy; Todor Vasiljevic; Neha Sharma; Conor J. Fitzpatrick; André Brodkorb; Thao T. Le; Lotte J. Knudsen; Lotte B. Larsen; Nina A. Poulsen (Food Chemistry, 2026)

Assessment of Fellowship Didactic Curricula in Hematology/Oncology: Cross-Sectional Findings From the PODCAST-HOF Trial - Ronak H. Mistry; Karine Tawagi; Daniel J. Hausrath; Samantha A. Armstrong; Inas A. Abuali; Ankoor N. Biswas; Srijan Valasapalli; Pranali S. Pachika; Moriah K. Forster; Ericson Stoen; Yurhee Lee; Giuliana G. Berardi; et al. (Journal of Cancer Education, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Trait-space disparity in fish communities spanning 380 million years from the Late Devonian to present - John Llewelyn; John A. Long; Richard Cloutier; Alice M. Clement; Giovanni Strona; Frédérik Saltré; Michael S.Y. Lee; Brian Choo; Kate Trinajstic; Olivia Vanhaesebroucke; Austin Fitzpatrick; Corey J.A. Bradshaw (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Evaluating uncertainties with sample-collection method and source selection in sediment fingerprinting: an example from a Great Lakes tributary - Tanja N. Williamson; James D. Blount; Heidi M. Broerman; Faith A. Fitzpatrick; Isaac J. Mevis; Dayle J. Hoefling; Shannon M. Pace; Matthew J. Komiskey; Rebecca M. Kreiling (Journal of Soils and Sediments, 2025)
Purpose Identifying suspended-sediment (SS) sources, seasonal variability, and phosphorus (P) transported with SS is critical information for basin managers, although there may be concerns about comparability between flow-integrated SS samples used for sediment fingerprinting and discrete samples used for concentrations and loads in basins where SS is mostly silt + clay and(or) one land-use predominates. Objectives were to determine if (1) sample-collection method and (2) source consideration influenced apportionment of the largest SS source. Methods Concurrent-replicate, SS samples were collected during 2022 from the East River, Wisconsin using an automated sampler, commonly used for water-quality sampling, and passive samplers, frequently used for SS fingerprinting. Samples were evaluated for differences in physical and chemical characteristics that may affect source apportionment. Considered sources included three upland land-use (cropland, forest, and roads), two in-channel (streambank and streambed sediment), and one that connects uplands to the stream channel (gullies). Source apportionment used established methods in the SedSAT tool. Source scenarios included land-use + streambank (4src), 4src + gully, 4src + streambed, and 4src + gully + streambed (6src). Results There were no statistically significant differences in median grain size, organic carbon, or sediment-bound P as a function of collection method. In-channel sources were the largest proportional SS source, regardless of season, hydrologic condition, collection method, or source scenario. Source verification highlighted which source fingerprints were most accurately defined and implications for SS target apportionment. Conclusion Varying the source scenarios for sediment fingerprinting indicated that improved management of hydrologic connectivity between upland land use and the stream channel has the potential to mitigate SS loads.

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

The challenge of reducing antimicrobial resistance (AMR) across the one health landscape: Diverse perspectives on AMR risks and their mitigation in sinks, drains, and wastewater - Hillary A. Craddock; Aoife Kearney; Fidelma Fitzpatrick; Caoimhe Finn; Mary T. Pryce; Deirdre Fitzgerald-Hughes (Science of The Total Environment, 2025)

Harvest legacies and climate change interact to shape forest structure and biomass through time - Lucien Fitzpatrick; Bailey A. Murphy; Meghan G. Midgley; Ankur R. Desai; Michael C. Dietze; Kurt Dreisilker; Christine R. Rollinson (Journal of Environmental Management, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Outreach & DNA-based monitoring facilitate 3-fold reduction in seafood mislabeling in Los Angeles over 10 years - Demian A. Willette; Kelli Andrade; Ben Fitzpatrick; Kesterlyn Wilson (Food Control, 2025)

Inpatient referrals to a specialist falls and syncope service: prevalence of STOPPFall FRIDs and review of deprescribing patterns - D. O’Donnell; T. Zainal; K. Malomo; N. Fitzpatrick; C. Rice; L. Byrne; R. Briggs; C. Cunningham; R. A. Kenny; A. H. Lavan (European Journal of Clinical Pharmacology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Cheddar cheese production, structure and in-vitro semi-dynamic gastric digestion: The role of β-casein phenotype - Davor Daniloski; Richard M. Page; Prabin Lamichhane; Conor J. Fitzpatrick; Todor Vasiljevic; André Brodkorb; Mark Timlin; John Paul Murphy; Tom F. O'Callaghan; Noel A. McCarthy (Food Research International, 2024)

Finite element modeling of the glass sealing process for solid oxide cell stacks - James Fitzpatrick; Kerry Meinhardt; Naveen Karri; Brian Koeppel; Jie Bao; Tongan Jin; Lorraine Seymour; Nathan Royer; Olga A. Marina (Chemical Engineering Journal, 2024)

P07-09 Spatio-temporal multi-omics analysis of lung tissue and matched biofluids identifies circulatory safety biomarkers for monitoring inhaled drug induced lung injury - M.M. Majumder; E. Williams; M.O. Lindvall; A. Jarnuczak; G. Hamm; C. Di Poto; A.A. Iannetta; J.L. Touza; E.L. Allman; E. Miele; J. Lindgren; E. Sand; et al. (Toxicology Letters, 2024)

A novel in vitro high-content imaging assay for the prediction of drug-induced lung toxicity - Paul A. Fitzpatrick; Julia Johansson; Gareth Maglennon; Ian Wallace; Ramon Hendrickx; Marianna Stamou; Kinga Balogh Sivars; Susann Busch; Linnea Johansson; Natalie Van Zuydam; Kelley Patten; Per M. Åberg; et al. (Archives of Toxicology, 2024)
The development of inhaled drugs for respiratory diseases is frequently impacted by lung pathology in non-clinical safety studies. To enable design of novel candidate drugs with the right safety profile, predictive in vitro lung toxicity assays are required that can be applied during drug discovery for early hazard identification and mitigation. Here, we describe a novel high-content imaging-based screening assay that allows for quantification of the tight junction protein occludin in A549 cells, as a model for lung epithelial barrier integrity. We assessed a set of compounds with a known lung safety profile, defined by clinical safety or non-clinical in vivo toxicology data, and were able to correctly identify 9 of 10 compounds with a respiratory safety risk and 9 of 9 compounds without a respiratory safety risk (90% sensitivity, 100% specificity). The assay was sensitive at relevant compound concentrations to influence medicinal chemistry optimization programs and, with an accessible cell model in a 96-well plate format, short protocol and application of automated imaging analysis algorithms, this assay can be readily integrated in routine discovery safety screening to identify and mitigate respiratory toxicity early during drug discovery. Interestingly, when we applied physiologically-based pharmacokinetic (PBPK) modelling to predict epithelial lining fluid exposures of the respiratory tract after inhalation, we found a robust correlation between in vitro occludin assay data and lung pathology in vivo, suggesting the assay can inform translational risk assessment for inhaled small molecules.

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Genetic structure of restored Brook Trout populations in the Southern Appalachian Mountains indicates successful reintroductions - Rebecca J. Smith; David C. Kazyak; Matt A. Kulp; Barbara A. Lubinski; Benjamin M. Fitzpatrick (Conservation Genetics, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Genomic insights into hybrid zone formation: The role of climate, landscape, and demography in the emergence of a novel hybrid lineage - Constance E. Bolte; Tommy Phannareth; Michelle Zavala‐Paez; Brianna N. Sutara; Muhammed F. Can; Matthew C. Fitzpatrick; Jason A. Holliday; Stephen R. Keller; Jill A. Hamilton (Molecular Ecology, 2024)
Population demographic changes, alongside landscape, geographic and climate heterogeneity, can influence the timing, stability and extent of introgression where species hybridise. Thus, quantifying interactions across diverged lineages, and the relative contributions of interspecific genetic exchange and selection to divergence at the genome‐wide level is needed to better understand the drivers of hybrid zone formation and maintenance. We used seven latitudinally arrayed transects to quantify the contributions of climate, geography and landscape features to broad patterns of genetic structure across the hybrid zone of Populus trichocarpa and P. balsamifera and evaluated the demographic context of hybridisation over time. We found genetic structure differed among the seven transects. While ancestry was structured by climate, landscape features influenced gene flow dynamics. Demographic models indicated a secondary contact event may have influenced contemporary hybrid zone formation with the origin of a putative hybrid lineage that inhabits regions with higher aridity than either of the ancestral groups. Phylogenetic relationships based on chloroplast genomes support the origin of this hybrid lineage inferred from demographic models based on the nuclear data. Our results point towards the importance of climate and landscape patterns in structuring the contact zones between P. trichocarpa and P. balsamifera and emphasise the value whole genome sequencing can have to advancing our understanding of how neutral processes influence divergence across space and time.

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Sediment budget of a Maumee River headwater tributary: how streambank erosion, streambed-sediment storage, and streambed-sediment source inform our understanding of legacy phosphorus - Tanja N. Williamson; Faith A. Fitzpatrick; Rebecca M. Kreiling; James D. Blount; Diana L. Karwan (Journal of Soils and Sediments, 2024)
Objective We described source and phosphorus (P) retention potential of soft, fine-grained, streambed sediment and associated phosphorus (sed-P) during summer low-flow conditions. Combining in-channel, sed-P storage with relative age provided context on relevance to western Lake Erie Basin management goals. Methods In 2019, rapid geomorphic assessment (30 reaches) compared streambed-sediment storage (S) to streambank erosion (E), providing annual sediment budgets (S:E). Streambed sediment (13 reaches) was fingerprinted and analyzed for sed-P. The P saturation ratio (PSR; four reaches) quantified potential sorption/desorption of dissolved P (DP) between the water column and streambed sediment. Analyses were supplemented with data from 2017 and 2021. The ratio of two fallout radionuclides, beryllium-7 (54-day half-life) and excess lead-210 (22.3 years), apportioned “new” sediment based on time since rainfall contact. Results Streambed sediment was mostly streambank (54–96%) for contributing areas > 2.7 km 2 ; for upstream reaches, a larger percentage was apportioned as upland (cropland, pasture, forest, and road), with < 30% streambank. Streambank erosion correlated with contributing area; however, soil type (ecoregion), stream characteristics, and land use combined to drive streambed-sediment storage. Individual-reach S:E (accumulation of 0.01–35 years of streambank erosion) differentiated erosional and depositional in-channel environments. Most reaches indicated that 17–57% of sediment had recent contact with rainfall. Streambed-sediment PSR indicated a low potential for further sorption of DP from the water column; one reach was a P source when sampled. Conclusion Sed-P was higher in streambed sediment than in source samples, which varied by land use and ecoregion. This indicates homogenization resulting from in-stream sorption of DP during sediment transport that occurs over multiple events.

Parentage‐based tagging using mothers balances accuracy and cost for discriminating between natural and stocked recruitment for inland fisheries - Kimberly B. Fitzpatrick; Nina Overgaard Therkildsen; Benjamin Marcy‐Quay; Harmony B. Borchardt‐Wier; Suresh A. Sethi (Fisheries Management and Ecology, 2023)
Hatchery programmes are frequently used to supplement inland fisheries, yet achieving successful management outcomes often requires information on stocked versus naturally reproduced fish abundance. Parentage‐based tagging – genetically assigning offspring to their parents – has potential to be an effective approach for distinguishing stocked and naturally reproduced fish. However, several challenges may limit its application to inland fisheries, including genetic relatedness among populations that can affect identification accuracy and high costs of genotyping large broodstocks. Here, we demonstrate the efficacy of parentage‐based tagging based on broodmothers in the Lake Ontario Chinook Salmon fishery, which uses thousands of broodparents and has potential for substantial relatedness between stocked and naturally reproduced fish. Restricting parent sampling to broodmothers reduced costs by two‐thirds, was logistically pragmatic, and achieved >95% accuracy in distinguishing stocked from naturally reproduced salmon. Combined, these results highlight the potential wide applicability of parentage‐based tagging for assessing stocking programmes in inland waters.

Pedicle Screw Placement Accuracy in Robot-Assisted Spinal Fusion in a Multicenter Study - Victoria L. Volk; Keegan A. Steele; Mia Cinello-Smith; Richard V. Chua; John Pollina; Gregory Poulter; Eiman Shafa; Peter Busselberg; Clare K. Fitzpatrick (Annals of Biomedical Engineering, 2023)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Development of an Interprofessional Small Bowel Placement Training Program - A. Fitzpatrick; M. Houser; C. Fackler; A. Patton; K. Roberts (Journal of the Academy of Nutrition and Dietetics, 2023)

Recombinant production, characterization and industrial application testing of a novel acidic exo/endo-chitinase from Rasamsonia emersonii - Kelly Dwyer; Ian S. Bentley; David A. Fitzpatrick; Aliabbas A. Saleh; Emma Tighe; Eibhilin McGleenan; Darragh Gaffney; Gary Walsh (Extremophiles, 2023)

Building a library of source samples for sediment fingerprinting – Potential and proof of concept - Tanja N. Williamson; Faith A. Fitzpatrick; Rebecca M. Kreiling (Journal of Environmental Management, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

On the application of rainfall projections from a convection-permitting climate model to lumped catchment models - M.J. Ascott; V. Christelis; D.J. Lapworth; D.M.J. Macdonald; C. Tindimugaya; A. Iragena; D. Finney; R. Fitzpatrick; J.H. Marsham; D.P. Rowell (Journal of Hydrology, 2023)

Elevated Winter Stream Temperatures below Wastewater Treatment Plants Shift Reproductive Development of Female Johnny Darter Etheostoma nigrum: A Field and Histologic Approach - Catherine M. Adams; Dana L. Winkelman; Paula A. Schaffer; Daniel L. Villeneuve; Jenna E. Cavallin; Michael Ellman; Kelvin Santana Rodriguez; Ryan M. Fitzpatrick (Fishes, 2022)
River water temperatures are increasing globally, particularly in urban systems. In winter, wastewater treatment plant (WWTP) effluent inputs are of particular concern because they increase water temperatures from near freezing to ~7–15 °C. Recent laboratory studies suggest that warm overwinter temperatures impact the reproductive timing of some fishes. To evaluate winter water temperature’s influence in the wild, we sampled Johnny Darter Etheostoma nigrum from three urban South Platte River tributaries in Colorado upstream and downstream of WWTP effluent discharge sites. Fish were collected weekly during the spring spawning season of 2021 and reproductive development was determined from histological analysis of the gonads. Winter water temperatures were approximately 5–10 °C greater ~300 m downstream of the WWTP effluent compared to upstream sites, and approximately 3 °C warmer at sampling sites ~5000 m downstream of the effluent discharge. Females collected downstream of WWTP effluent experienced accelerated reproductive development compared to upstream by 1–2 weeks. Water quality, including total estrogenicity, and spring water temperatures did not appear to explain varying reproductive development. It appears that small increases in winter water temperature influence the reproductive timing in E. nigrum. Further investigations into how shifts in reproductive timing influence other population dynamics are warranted.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2022)

Sex‐specific inbreeding depression: A meta‐analysis - Regina Vega‐Trejo; Raïssa A. de Boer; John L. Fitzpatrick; Alexander Kotrschal (Ecology Letters, 2022)
Inbreeding depression, the reduced fitness of the offspring of related individuals, can affect males and females differently. Although a comprehensive theoretical framework describing the causes of sex‐specific inbreeding depression is lacking, empirical evidence suggests that often one sex tends to be more vulnerable than the other. However, the generality, direction, and degree of sex‐specific difference in inbreeding depression remains enigmatic as studies on this topic have reported conflicting results. Here, we conduct a meta‐analysis to test for sex‐specific differences in the magnitude of inbreeding depression. We synthetised 321 effect sizes of experimental studies across 47 species and found a small difference in inbreeding depression between the sexes: females suffered slightly higher inbreeding depression than males. Furthermore, a higher inbreeding coefficient was correlated with higher inbreeding depression. However, there was a large amount of heterogeneity that remained unexplained, even when considering different factors that could affect inbreeding between the sexes, such as sexual size dimorphism, heterogamety, the type of trait measured and whether animals were tested in a stressful environment. As such, we highlight the need to further explore inbreeding depression across different species to determine the occurrence and causes of sex differences to increase our understanding of the evolutionary consequences of sex‐specific inbreeding depression.

Tag retention in and effects of passive integrated transponder tagging on survival and swimming performance of a small‐bodied darter - Tyler R. Swarr; Christopher A. Myrick; Ryan M. Fitzpatrick (Journal of Fish Biology, 2022)
Fisheries biologists have been hesitant to use passive integrated transponder (PIT) tags in small‐bodied fishes (40–200 mm TL) such as darters (Percidae: Etheostomatinae) because of the fishes' size and potential effect on swimming performance. The authors used constant acceleration trials to evaluate the swimming performance of Arkansas darters Etheostoma cragini in control (no incision or tag), sham (incision and suture) or PIT tagged (surgically implanted 8 × 1.4 mm intra‐peritoneal PIT tag) treatments. Tag retention and fish survival were monitored for up to 199 days post‐tagging. Maximum swimming velocity did not differ between control, sham and PIT tag treatments, nor was maximum swimming velocity affected by the tagging procedure. Tag retention was 100%, and the overall survival of tagged fish was 88% in the swimming study, and 100% in the long‐term study, suggesting that small PIT tags are suitable for use in darters. The authors include a brief meta‐analysis on the results reported by 20 studies that PIT tagged small‐bodied fishes, representing 38 species and nine families of freshwater fish.

Biomarkers Based on Comprehensive Hierarchical EEG Coherence Analysis: Example Application to Social Competence in Autism (Preliminary Results) - Mo Modarres; David Cochran; David N. Kennedy; Richard Schmidt; Paula Fitzpatrick; Jean A. Frazier (Neuroinformatics, 2022)

Disease-Relevant Single Cell Photonic Signatures Identify S100β Stem Cells and their Myogenic Progeny in Vascular Lesions - Claire Molony; Damien King; Mariana Di Luca; Michael Kitching; Abidemi Olayinka; Roya Hakimjavadi; Lourdes A. N. Julius; Emma Fitzpatrick; Yusof Gusti; Denise Burtenshaw; Killian Healy; Emma K. Finlay; et al. (Stem Cell Reviews and Reports, 2021)
A hallmark of subclinical atherosclerosis is the accumulation of vascular smooth muscle cell (SMC)-like cells leading to intimal thickening and lesion formation. While medial SMCs contribute to vascular lesions, the involvement of resident vascular stem cells (vSCs) remains unclear. We evaluated single cell photonics as a discriminator of cell phenotype in vitro before the presence of vSC within vascular lesions was assessed ex vivo using supervised machine learning and further validated using lineage tracing analysis . Using a novel lab-on-a-Disk(Load) platform, label-free single cell photonic emissions from normal and injured vessels ex vivo were interrogated and compared to freshly isolated aortic SMCs, cultured Movas SMCs, macrophages, B-cells, S100β + mVSc, bone marrow derived mesenchymal stem cells (MSC) and their respective myogenic progeny across five broadband light wavelengths (λ465 - λ670 ± 20 nm). We found that profiles were of sufficient coverage, specificity, and quality to clearly distinguish medial SMCs from different vascular beds (carotid vs aorta), discriminate normal carotid medial SMCs from lesional SMC-like cells ex vivo following flow restriction , and identify SMC differentiation of a series of multipotent stem cells following treatment with transforming growth factor beta 1 (TGF- β1), the Notch ligand Jagged1, and Sonic Hedgehog using multivariate analysis, in part, due to photonic emissions from enhanced collagen III and elastin expression. Supervised machine learning supported genetic lineage tracing analysis of S100β + vSCs and identified the presence of S100β + vSC-derived myogenic progeny within vascular lesions. We conclude disease-relevant photonic signatures may have predictive value for vascular disease. Graphical abstract

Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2021)

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Snowpack, Tree Size, and Ecological Legacies Promote Seedling Establishment in Tree Islands at the Treeline - O. T. Fitzpatrick; M. Blade; L. A. Fishback; G. P. Kershaw; J. Muffly; S. D. Mamet (Ecosystems, 2020)

Delineation of phenotypes and genotypes related to cohesin structural protein RAD21 - Lianne C. Krab; Iñigo Marcos-Alcalde; Melissa Assaf; Meena Balasubramanian; Janne Bayer Andersen; Anne-Marie Bisgaard; David R. Fitzpatrick; Sanna Gudmundsson; Sylvia A. Huisman; Tugba Kalayci; Saskia M. Maas; Francisco Martinez; et al. (Human Genetics, 2020)
RAD21 encodes a key component of the cohesin complex, and variants in RAD21 have been associated with Cornelia de Lange Syndrome (CdLS). Limited information on phenotypes attributable to RAD21 variants and genotype–phenotype relationships is currently published. We gathered a series of 49 individuals from 33 families with RAD21 alterations [24 different intragenic sequence variants (2 recurrent), 7 unique microdeletions], including 24 hitherto unpublished cases. We evaluated consequences of 12 intragenic variants by protein modelling and molecular dynamic studies. Full clinical information was available for 29 individuals. Their phenotype is an attenuated CdLS phenotype compared to that caused by variants in NIPBL or SMC1A for facial morphology, limb anomalies, and especially for cognition and behavior. In the 20 individuals with limited clinical information, additional phenotypes include Mungan syndrome (in patients with biallelic variants) and holoprosencephaly, with or without CdLS characteristics. We describe several additional cases with phenotypes including sclerocornea, in which involvement of the RAD21 variant is uncertain. Variants were frequently familial, and genotype–phenotype analyses demonstrated striking interfamilial and intrafamilial variability. Careful phenotyping is essential in interpreting consequences of RAD21 variants, and protein modeling and dynamics can be helpful in determining pathogenicity. The current study should be helpful when counseling families with a RAD21 variation.

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Temperature and telomeres: thermal treatment influences telomere dynamics through a complex interplay of cellular processes in a cold-climate skink - L. J. Fitzpatrick; M. Olsson; L. M. Parsley; A. Pauliny; T. L. Pinfold; T. Pirtle; G. M. While; E. Wapstra (Oecologia, 2019)

The genetic architecture of aniridia and Gillespie syndrome - Hildegard Nikki Hall; Kathleen A. Williamson; David R. FitzPatrick (Human Genetics, 2019)

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Comparison of bonobo and chimpanzee brain microstructure reveals differences in socio-emotional circuits - Habon A. Issa; Nicky Staes; Sophia Diggs-Galligan; Cheryl D. Stimpson; Annette Gendron-Fitzpatrick; Jared P. Taglialatela; Patrick R. Hof; William D. Hopkins; Chet C. Sherwood (Brain Structure and Function, 2019)

Restoration of wetlands: successes and failures on scalds comprising an iron oxide clogged layer with areas of acid sulfate soils - W. K. Gardner; R.W. Fitzpatrick; C. A. Hindhaugh (Plant and Soil, 2018)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

An experimental test of alternative population augmentation scenarios - John A. Kronenberger; Jill C. Gerberich; Sarah W. Fitzpatrick; E. Dale Broder; Lisa M. Angeloni; W. Chris Funk (Conservation Biology, 2018)
Human land use is fragmenting habitats worldwide and inhibiting dispersal among previously connected populations of organisms, often leading to inbreeding depression and reduced evolutionary potential in the face of rapid environmental change. To combat this augmentation of isolated populations with immigrants is sometimes used to facilitate demographic and genetic rescue. Augmentation with immigrants that are genetically and adaptively similar to the target population effectively increases population fitness, but if immigrants are very genetically or adaptively divergent, augmentation can lead to outbreeding depression. Despite well‐cited guidelines for the best practice selection of immigrant sources, often only highly divergent populations remain, and experimental tests of these riskier augmentation scenarios are essentially nonexistent. We conducted a mesocosm experiment with Trinidadian guppies (Poecilia reticulata) to test the multigenerational demographic and genetic effects of augmenting 2 target populations with 3 types of divergent immigrants. We found no evidence of demographic rescue, but we did observe genetic rescue in one population. Divergent immigrant treatments tended to maintain greater genetic diversity, abundance, and hybrid fitness than controls that received immigrants from the source used to seed the mesocosms. In the second population, divergent immigrants had a slightly negative effect in one treatment, and the benefits of augmentation were less apparent overall, likely because this population started with higher genetic diversity and a lower reproductive rate that limited genetic admixture. Our results add to a growing consensus that gene flow can increase population fitness even when immigrants are more highly divergent and may help reduce uncertainty about the use of augmentation in conservation.

Hepatocyte transplantation and advancements in alternative cell sources for liver-based regenerative medicine - Charlotte A Lee; Siddharth Sinha; Emer Fitzpatrick; Anil Dhawan (Journal of Molecular Medicine, 2018)

A hierarchical Bayesian model to incorporate uncertainty into methods for diversity partitioning - Zachary H. Marion; James A. Fordyce; Benjamin M. Fitzpatrick (Ecology, 2018)
Recently there have been major theoretical advances in the quantification and partitioning of diversity within and among communities, regions, and ecosystems. However, applying those advances to real data remains a challenge. Ecologists often end up describing their samples rather than estimating the diversity components of an underlying study system, and existing approaches do not easily provide statistical frameworks for testing ecological questions. Here we offer one avenue to do all of the above using a hierarchical Bayesian approach. We estimate posterior distributions of the underlying “true” relative abundances of each species within each unit sampled. These posterior estimates of relative abundance can then be used with existing formulae to estimate and partition diversity. The result is a posterior distribution of diversity metrics describing our knowledge (or beliefs) about the study system. This approach intuitively leads to statistical inferences addressing biologically motivated hypotheses via Bayesian model comparison. Using simulations, we demonstrate that our approach does as well or better at approximating the “true” diversity of a community relative to naïve or ad‐hoc bias‐corrected estimates. Moreover, model comparison correctly distinguishes between alternative hypotheses about the distribution of diversity within and among samples. Finally, we use an empirical ecological dataset to illustrate how the approach can be used to address questions about the makeup and diversities of assemblages at local and regional scales.

Analysis of the Impact of CD200 on Phagocytosis - Anthony Lyons; Aedín M. Minogue; Raasay S. Jones; Orla Fitzpatrick; Janis Noonan; Veronica A. Campbell; Marina A. Lynch (Molecular Neurobiology, 2017)

Pairwise beta diversity resolves an underappreciated source of confusion in calculating species turnover - Zachary H. Marion; James A. Fordyce; Benjamin M. Fitzpatrick (Ecology, 2017)
Beta diversity is an important metric in ecology quantifying differentiation or disparity in composition among communities, ecosystems, or phenotypes. To compare systems with different sizes ( N , number of units within a system), beta diversity is often converted to related indices such as turnover or local/regional differentiation. Here we use simulations to demonstrate that these naive measures of dissimilarity depend on sample size and design. We show that when N is the number of sampled units (e.g., quadrats) rather than the “true” number of communities in the system (if such exists), these differentiation measures are biased estimators. We propose using average pairwise dissimilarity as an intuitive solution. That is, instead of attempting to estimate an N ‐community measure, we advocate estimating the expected dissimilarity between any random pair of communities (or sampling units)—especially when the “true” N is unknown or undefined. Fortunately, measures of pairwise dissimilarity or overlap have been used in ecology for decades, and their properties are well known. Using the same simulations, we show that average pairwise metrics give consistent and unbiased estimates regardless of the number of survey units sampled. We advocate pairwise dissimilarity as a general standardization to ensure commensurability of different study systems.

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

Theory of Visual Attention (TVA) applied to mice in the 5-choice serial reaction time task - C. M. Fitzpatrick; M. Caballero-Puntiverio; U. Gether; T. Habekost; C. Bundesen; S. Vangkilde; D. P. D. Woldbye; J. T. Andreasen; A. Petersen (Psychopharmacology, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Quantitative magnetic resonance imaging in patients with cirrhosis: a cross-sectional study - Vijay P. B. Grover; Mary M. E. Crossey; Julie A. Fitzpatrick; Brian K. Saxby; Roberta Shaw; Adam D. Waldman; Marsha Y. Morgan; Simon D. Taylor-Robinson (Metabolic Brain Disease, 2016)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

Behavioral evidence suggests facultative scavenging by a marine apex predator during a food pulse - Neil Hammerschlag; Ian Bell; Richard Fitzpatrick; Austin J. Gallagher; Lucy A. Hawkes; Mark G. Meekan; John D. Stevens; Michele Thums; Matthew J. Witt; Adam Barnett (Behavioral Ecology and Sociobiology, 2016)

Exercise training comprising of single 20-s cycle sprints does not provide a sufficient stimulus for improving maximal aerobic capacity in sedentary individuals - P. Songsorn; A. Lambeth-Mansell; J. L. Mair; M. Haggett; B. L. Fitzpatrick; J. Ruffino; A. Holliday; R. S. Metcalfe; N. B. J. Vollaard (European Journal of Applied Physiology, 2016)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

The importance of plant genotype and contemporary evolution for terrestrial ecosystem processes - Connor R. Fitzpatrick; Anurag A. Agrawal; Nathan Basiliko; Amy P. Hastings; Marney E. Isaac; Michael Preston; Marc T. J. Johnson (Ecology, 2015)
Plant genetic variation and evolutionary dynamics are predicted to impact ecosystem processes but these effects are poorly understood. Here we test the hypothesis that plant genotype and contemporary evolution influence the flux of energy and nutrients through soil, which then feedback to affect seedling performance in subsequent generations. We conducted a multiyear field evolution experiment using the native biennial plant Oenothera biennis . This experiment was coupled with experimental assays to address our hypothesis and quantify the relative importance of evolutionary and ecological factors on multiple ecosystem processes. Plant genotype, contemporary evolution, spatial variation, and herbivory affected ecosystem processes (e.g., leaf decay, soil respiration, seedling performance, N cycling), but their relative importance varied between specific ecosystem variables. Insect herbivory and evolution also contributed to a feedback that affected seedling biomass of O. biennis in the next generation. Our results show that heritable variation among plant genotypes can be an important factor affecting local ecosystem processes, and while effects of contemporary evolution were detectable and sometimes strong, they were often contingent on other ecological factors.

Locally adapted traits maintained in the face of high gene flow - S. W. Fitzpatrick; J. C. Gerberich; J. A. Kronenberger; L. M. Angeloni; W. C. Funk (Ecology Letters, 2015)
Gene flow between phenotypically divergent populations can disrupt local adaptation or, alternatively, may stimulate adaptive evolution by increasing genetic variation. We capitalised on historical Trinidadian guppy transplant experiments to test the phenotypic effects of increased gene flow caused by replicated introductions of adaptively divergent guppies, which were translocated from high‐ to low‐predation environments. We sampled two native populations prior to the onset of gene flow, six historic introduction sites, introduction sources and multiple downstream points in each basin. Extensive gene flow from introductions occurred in all streams, yet adaptive phenotypic divergence across a gradient in predation level was maintained. Descendants of guppies from a high‐predation source site showed high phenotypic similarity with native low‐predation guppies in as few as ~12 generations after gene flow, likely through a combination of adaptive evolution and phenotypic plasticity. Our results demonstrate that locally adapted phenotypes can be maintained despite extensive gene flow from divergent populations.

Thermal stress response in a dinoflagellate-bearing nudibranch and the octocoral on which it feeds - Maren Ziegler; Shannon K. FitzPatrick; Ingo Burghardt; Katie L. Liberatore; A. Joshua Leffler; Cristina Takacs-Vesbach; Ursula Shepherd (Coral Reefs, 2014)

Adult vascular smooth muscle cells in culture express neural stem cell markers typical of resident multipotent vascular stem cells - Eimear Kennedy; Ciaran J. Mooney; Roya Hakimjavadi; Emma Fitzpatrick; Shaunta Guha; Laura E. Collins; Christine E. Loscher; David Morrow; Eileen M. Redmond; Paul A. Cahill (Cell and Tissue Research, 2014)

Hydrology and climatology at Laguna La Gaiba, lowland Bolivia: complex responses to climatic forcings over the last 25 000 years - SARAH E. METCALFE; BRONWEN S. WHITNEY; KATHARINE A. FITZPATRICK; FRANCIS E. MAYLE; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; DAVID G. MANN (Journal of Quaternary Science, 2014)
Diatom, geochemical and isotopic data provide a record of environmental change in Laguna La Gaiba, lowland Bolivia (17°45′S, 57°35′W), over the last ca. 25 000 years. High‐resolution diatom analysis around the Last Glacial–Interglacial Transition provides new insights into this period of change. The full and late glacial lake was generally quite shallow, but with evidence of periodic flooding. At about 13 100 cal a BP, just before the start of the Younger Dryas chronozone, the diatoms indicate shallower water conditions, but there is a marked change at about 12 200 cal a BP indicating the onset of a period of high variability, with rising water levels punctuated by periodic drying. From ca. 11 800 to 10 000 cal a BP, stable, deeper water conditions persisted. There is evidence for drying in the early to middle Holocene, but not as pronounced as that reported from elsewhere in the southern hemisphere tropics of South America. This was followed by the onset of wetter conditions in the late Holocene consistent with insolation forcing. Conditions very similar to present were established about 2100 cal a BP. A complex response to both insolation forcing and millennial‐scale events originating in the North Atlantic is noted.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Can genetic data confirm or refute historical records? The island invasion of the small Indian mongoose (Herpestes auropunctatus) - Arijana Barun; Matthew L. Niemiller; Benjamin M. Fitzpatrick; James A. Fordyce; Daniel Simberloff (Biological Invasions, 2013)

Characterization of 18 polymorphic microsatellite loci from invasive lionfish (Pterois volitans and P. miles) - Thomas F. Schultz; Cristin Keelin Fitzpatrick; D. Wilson Freshwater; James A. Morris (Conservation Genetics Resources, 2013)

Isolation and characterization of eight polymorphic microsatellite loci for Natterer’s bat, Myotis nattereri (Vespertilionidae, Chiroptera) - David D. Scott; Seán Fitzpatrick; Deborah A. Bailie; Emma S. M. Boston; Mathieu G. Lundy; Daniel J. Buckley; Emma C. Teeling; W. Ian Montgomery; Paulo A. Prodöhl (Conservation Genetics Resources, 2013)

Clinical and mutation data in 12 patients with the clinical diagnosis of Nager syndrome - J. C. Czeschik; C. Voigt; Y. Alanay; B. Albrecht; S. Avci; D. FitzPatrick; D. R. Goudie; U. Hehr; A. J. Hoogeboom; H. Kayserili; P. O. Simsek-Kiper; L. Klein-Hitpass; et al. (Human Genetics, 2013)

A comparative study of the molecular evolution of signalling pathway members across olfactory, gustatory and photosensory modalities - CHAO HE; DAVID A. FITZPATRICK; DAMIEN M. O’HALLORAN (Journal of Genetics, 2013)

Low temperature constrains growth rates but not short-term ingestion rates of Antarctic ciliates - Julie M. Rose; Elizabeth Fitzpatrick; Annie Wang; Rebecca J. Gast; David A. Caron (Polar Biology, 2013)

Populations of the Gall Midge Dasineura oxycoccana on Cranberry and Blueberry Produce and Respond to Different Sex Pheromones - Sheila M. Fitzpatrick; Regine Gries; Grigori Khaskin; Daniel A. H. Peach; Jessika Iwanski; Gerhard Gries (Journal of Chemical Ecology, 2013)

Symbiodinium diversity in the soft coral Heteroxenia sp. and its nudibranch predator Phyllodesmium lizardensis - S. K. FitzPatrick; K. L. Liberatore; J. R. Garcia; I. Burghardt; D. R. Colman; S. A. Moquin; C. D. Takacs-Vesbach; U. L. Shepherd (Coral Reefs, 2012)

Hybridization between two gartersnake species (Thamnophis) of conservation concern: a threat or an important natural interaction? - John S. Placyk; Benjamin M. Fitzpatrick; Gary S. Casper; Randall L. Small; R. Graham Reynolds; Daniel W. A. Noble; Ronald J. Brooks; Gordon M. Burghardt (Conservation Genetics, 2012)

What can DNA tell us about biological invasions? - Benjamin M. Fitzpatrick; James A. Fordyce; Matthew L. Niemiller; R. Graham Reynolds (Biological Invasions, 2012)

Reconstructing the Fungal Tree of Life Using Phylogenomics and a Preliminary Investigation of the Distribution of Yeast Prion-Like Proteins in the Fungal Kingdom - Edgar M. Medina; Gary W. Jones; David A. Fitzpatrick (Journal of Molecular Evolution, 2011)

Investigation of Design Space for Freeze-Drying: Use of Modeling for Primary Drying Segment of a Freeze-Drying Cycle - Venkat Rao Koganti; Evgenyi Y. Shalaev; Mark R. Berry; Thomas Osterberg; Maickel Youssef; David N. Hiebert; Frank A. Kanka; Martin Nolan; Rosemary Barrett; Gioval Scalzo; Gillian Fitzpatrick; Niall Fitzgibbon; et al. (AAPS PharmSciTech, 2011)

Development and characterization of 10 polymorphic microsatellite loci for the blue shark, Prionace glauca, and their cross shark-species amplification - Seán Fitzpatrick; Mahmood S. Shivji; Demian D. Chapman; Paulo A. Prodöhl (Conservation Genetics Resources, 2011)

A lover, not a fighter: mating causes male crickets to lose fights - Kevin A. Judge; Janice J. Ting; Jonathan Schneider; Mark J. Fitzpatrick (Behavioral Ecology and Sociobiology, 2010)

Ecological boundary detection using Bayesian areal wombling - Matthew C. Fitzpatrick; Evan L. Preisser; Adam Porter; Joseph Elkinton; Lance A. Waller; Bradley P. Carlin; Aaron M. Ellison (Ecology, 2010)
The study of ecological boundaries and their dynamics is of fundamental importance to much of ecology, biogeography, and evolution. Over the past two decades, boundary analysis (of which wombling is a subfield) has received considerable research attention, resulting in multiple approaches for the quantification of ecological boundaries. Nonetheless, few methods have been developed that can simultaneously (1) analyze spatially homogenized data sets (i.e., areal data in the form of polygons rather than point‐reference data); (2) account for spatial structure in these data and uncertainty associated with them; and (3) objectively assign probabilities to boundaries once detected. Here we describe the application of a Bayesian hierarchical framework for boundary detection developed in public health, which addresses these issues but which has seen limited application in ecology. As examples, we analyze simulated spread data and the historic pattern of spread of an invasive species, the hemlock woolly adelgid ( Adelges tsugae ), using county‐level summaries of the year of first reported infestation and several covariates potentially important to influencing the observed spread dynamics. Bayesian areal wombling is a promising approach for analyzing ecological boundaries and dynamics related to changes in the distributions of native and invasive species.

Analysis of genetic diversity in flowering dogwood natural stands using microsatellites: the effects of dogwood anthracnose - D. Hadziabdic; B. M. Fitzpatrick; X. Wang; P. A. Wadl; T. A. Rinehart; B. H. Ownley; M. T. Windham; R. N. Trigiano (Genetica, 2010)

Gene trees, species and species trees in the Ctenosaura palearis clade - Stesha A. Pasachnik; Arthur C. Echternacht; Benjamin M. Fitzpatrick (Conservation Genetics, 2010)

Public health impacts of climate change in Washington State: projected mortality risks due to heat events and air pollution - J. Elizabeth Jackson; Michael G. Yost; Catherine Karr; Cole Fitzpatrick; Brian K. Lamb; Serena H. Chung; Jack Chen; Jeremy Avise; Roger A. Rosenblatt; Richard A. Fenske (Climatic Change, 2010)

Development and environmental application of a genus-specific quantitative PCR approach for Pseudo-nitzschia species - Elizabeth Fitzpatrick; David A. Caron; Astrid Schnetzer (Marine Biology, 2010)

Evolution of flower shape in Plantago lanceolata - Wesley Reardon; David A. Fitzpatrick; Mario A. Fares; Jacqueline M. Nugent (Plant Molecular Biology, 2009)

Gene flow between an endangered endemic iguana, and its wide spread relative, on the island of Utila, Honduras: when is hybridization a threat? - Stesha A. Pasachnik; Benjamin M. Fitzpatrick; Thomas J. Near; Arthur C. Echternacht (Conservation Genetics, 2009)

C-reactive protein, interleukin-6, and prostate cancer risk in men aged 65 years and older - Brandon L. Pierce; Mary L. Biggs; Marvalyn DeCambre; Alexander P. Reiner; Christopher Li; Annette Fitzpatrick; Christopher S. Carlson; Janet L. Stanford; Melissa A. Austin (Cancer Causes & Control, 2009)

Geomorphology of a dryland fluvial system: the Lower Balonne River, southern Queensland - A. L. Kernich; C. F. Pain; J. D. A. Clarke; A. D. Fitzpatrick (Australian Journal of Earth Sciences, 2009)

Geographical variation in genetic structure of an Atlantic Coastal Forest frog reveals regional differences in habitat stability - SARAH W. FITZPATRICK; CINTHIA A. BRASILEIRO; CÉLIO F. B. HADDAD; KELLY R. ZAMUDIO (Molecular Ecology, 2009)
Climatic oscillations throughout the Pleistocene combined with geological and topographic complexity resulted in extreme habitat heterogeneity along the Atlantic coast of Brazil. Inferring how these historic landscape patterns have structured the current diversity of the region's biota is important both for our understanding of the factors promoting diversification, as well as the conservation of this biodiversity hotspot. Here we evaluate potential historical scenarios of diversification in the Atlantic Coastal Forest of Brazil by investigating the population genetic structure of a frog endemic to the region. Using mitochondrial and nuclear sequences, we generated a Bayesian population‐level phylogeny of the Thoropa miliaris species complex. We found deep genetic divergences among five geographically distinct clades. Southern clades were monophyletic and nested within paraphyletic northern clades. Analyses of historical demographic patterns suggest an overall north to south population expansion, likely associated with regional differences in habitat stability during the Pliocene and early Pleistocene. However, genetic structure among southern populations is less pronounced and likely represents more recent vicariant events resulting from Holocenic sea‐level oscillations. Our analyses corroborate that the Atlantic Coastal Forest has been a biogeographically dynamic landscape and suggest that the high diversity of its fauna and flora resulted from a combination of climatic and geologic events from the Pliocene to the present.

Mixed parentage in Neolamprologus pulcher groups - K. A. Stiver; J. L. Fitzpatrick; J. K. Desjardins; S. Balshine (Journal of Fish Biology, 2009)
Genetic data collected on co‐operatively breeding Neolamprologus pulcher groups from Lake Tanganyika revealed mixed parentage in 80% of the groups examined. A case (1/11) of shared maternity was detected where a subordinate female bred alongside the dominant female in a social group. Extra‐pair paternity was assigned to other dominant males who held their own social groups, but subordinate males were not found to father young in any group (0/9).

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Lines of Evidence for Horizontal Gene Transfer of a Phenazine Producing Operon into Multiple Bacterial Species - David A. Fitzpatrick (Journal of Molecular Evolution, 2009)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Environmental Impact Assessment Under the Mackenzie Valley Resource Management Act: Deliberative Democracy in Canada’s North? - Patricia Fitzpatrick; A. John Sinclair; Bruce Mitchell (Environmental Management, 2008)

The strontium content of roe collected from spawning brown trout Salmo trutta L. reflects recent otolith microchemistry - E. M. Waite; G. P. Closs; J. Kim; B. Barry; A. Markwitz; R. Fitzpatrick (Journal of Fish Biology, 2008)
The relationship between the strontium content of the outer layers of otoliths (an indication of recent marine, estuarine or riverine habitat use) and the strontium content of roe in ripe female brown trout Salmo trutta was examined in fish collected from the Pomahaka River and the lower reaches of the Clutha River, South Island, New Zealand. A close relationship was found between the strontium content of roe and the outer layers of otoliths. This finding suggests that spawned eggs collected from redds could potentially be used to track the extent of upstream spawning migrations by anadromous brown trout.

Congruent population structure inferred from dispersal behaviour and intensive genetic surveys of the threatened Florida scrub‐jay ( Aphelocoma cœrulescens ) - A. COULON; J. W. FITZPATRICK; R. BOWMAN; B. M. STITH; C. A. MAKAREWICH; L. M. STENZLER; I. J. LOVETTE (Molecular Ecology, 2008)
The delimitation of populations, defined as groups of individuals linked by gene flow, is possible by the analysis of genetic markers and also by spatial models based on dispersal probabilities across a landscape. We combined these two complimentary methods to define the spatial pattern of genetic structure among remaining populations of the threatened Florida scrub‐jay, a species for which dispersal ability is unusually well‐characterized. The range‐wide population was intensively censused in the 1990s, and a metapopulation model defined population boundaries based on predicted dispersal‐mediated demographic connectivity. We subjected genotypes from more than 1000 individual jays screened at 20 microsatellite loci to two Bayesian clustering methods. We describe a consensus method for identifying common features across many replicated clustering runs. Ten genetically differentiated groups exist across the present‐day range of the Florida scrub‐jay. These groups are largely consistent with the dispersal‐defined metapopulations, which assume very limited dispersal ability. Some genetic groups comprise more than one metapopulation, likely because these genetically similar metapopulations were sundered only recently by habitat alteration. The combined reconstructions of population structure based on genetics and dispersal‐mediated demographic connectivity provide a robust depiction of the current genetic and demographic organization of this species, reflecting past and present levels of dispersal among occupied habitat patches. The differentiation of populations into 10 genetic groups adds urgency to management efforts aimed at preserving what remains of genetic variation in this dwindling species, by maintaining viable populations of all genetically differentiated and geographically isolated populations.

Sex and status in a cooperative breeding fish: behavior and androgens - Julie K. Desjardins; Kelly A. Stiver; John L. Fitzpatrick; Nicole Milligan; Glen J. Van Der Kraak; Sigal Balshine (Behavioral Ecology and Sociobiology, 2008)

Evidence for size and sex‐specific dispersal in a cooperatively breeding cichlid fish - K. A. STIVER; J. K. DESJARDINS; J. L. FITZPATRICK; B. NEFF; J. S. QUINN; S. BALSHINE (Molecular Ecology, 2007)
African Great Lake cichlid populations are divided into thousands of genetic subpopulations. The low gene flow between these subpopulations is thought to result from high degrees of natal philopatry, heavy predation pressure, and a patchy distribution of preferred habitats. While predation pressure and habitat distribution are fairly straightforward to assess, data on dispersal distances and rates are scarce. In fishes, direct observations of dispersal events are unlikely, but dispersal can be studied using molecular markers. Using seven microsatellite loci, we examined dispersal in the cooperatively breeding cichlid fish, Neolamprologus pulcher . As this species is found in well‐defined groups clustered into subpopulations, we could assess dispersal on a narrow (within subpopulation) and broad (between subpopulation) scale. While fish were generally more related to others in their own subpopulation than they were to fish from other subpopulations, large males diverged from this pattern. Large males were more related to other large males from different subpopulations than they were to large males from their own subpopulation, suggesting more frequent dispersal by large males. Across subpopulations, relatedness between large males was higher than the relatedness among large females; this pattern was not detected in small males and small females. Within a subpopulation, individuals appeared to be preferentially moving away from relatives, and movement was unrestricted by the physical distance between groups. Our results highlight the importance of examining multiple spatial scales when studying individual dispersal biases.

Mutations in autism susceptibility candidate 2 (AUTS2) in patients with mental retardation - Vera M. Kalscheuer; David FitzPatrick; Niels Tommerup; Merete Bugge; Erik Niebuhr; Luitgard M. Neumann; Andreas Tzschach; Sarah A. Shoichet; Corinna Menzel; Fikret Erdogan; Ger Arkesteijn; Hans-Hilger Ropers; et al. (Human Genetics, 2007)

A gene family of putative immune recognition molecules in the hydroid Hydractinia - Ryan S. Schwarz; Linda Hodes-Villamar; Kelly A. Fitzpatrick; Matthew G. Fain; Austin L. Hughes; Luis F. Cadavid (Immunogenetics, 2007)

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)

The Molecular Phylogeny of a Nematode-Specific Clade of Heterotrimeric G-Protein α-Subunit Genes - Damien M. O’Halloran; David A. Fitzpatrick; Grace P. McCormack; James O. McInerney; Ann M. Burnell (Journal of Molecular Evolution, 2006)

Adult Emperor angelfish (Pomacanthus imperator) clean Giant sunfishes (Mola mola) at Nusa Lembongan, Indonesia - N. Konow; R. Fitzpatrick; A. Barnett (Coral Reefs, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Genetic Susceptibility to Prostate Cancer: Prostate-specific Antigen and its Interaction with the Androgen Receptor (United States) - Weiva Sieh; Karen L. Edwards; Annette L. Fitzpatrick; Sengkeo L. Srinouanprachanh; Fred M. Farin; Stephanie A. Monks; Richard A. Kronmal; David L. Eaton (Cancer Causes & Control, 2006)

Evidence of Positive Darwinian Selection in Putative Meningococcal Vaccine Antigens - David A. Fitzpatrick; Christopher J. Creevey; James O. McInerney (Journal of Molecular Evolution, 2005)

The formation, vacuolar localization, and tonoplast transport of salicylic acid glucose conjugates in tobacco cell suspension cultures - John V. Dean; Leila A. Mohammed; Terry Fitzpatrick (Planta, 2005)

Evidence of Positive Darwinian Selection in Omp85, a Highly ConservedBacterial Outer Membrane Protein Essential for Cell Viability - David A. Fitzpatrick; James O. McInerney (Journal of Molecular Evolution, 2005)

Differentiation-induced HL-60 cell apoptosis: A mechanism independent of mitochondrial disruption? - B. T. Doyle; A. J. O’Neill; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2004)

Molecular phylogeography of the Amazonian Chagas disease vectors Rhodnius prolixus and R. robustus - Fernando A. Monteiro; Toby V. Barrett; Sinead Fitzpatrick; Celia Cordon‐Rosales; Dora Feliciangeli; Charles B. Beard (Molecular Ecology, 2003)
The phylogeographical structure of the closely related species Rhodnius prolixus and R. robustus is presented based on a 663‐base pair (bp) fragment of the mitochondrial cytochrome b gene. Twenty haplotypes were recovered from 84 samples examined, representing 26 populations from seven Latin American countries. The resulting phylogenetic tree is composed of five major reciprocally monophyletic clades, one representing R. prolixus and four representing R. robustus . While R. prolixus is a very homogeneous assemblage, R. robustus has deeper clades and is paraphyletic, with the clade comprising R. robustus from Venezuela (Orinoco region) more closely related to the R. prolixus clade than to the other R. robustus populations from the Amazon region. The R. robustus paraphyly was supported further by the analysis of a nuclear gene (D2 region of the 28S RNA) for a subset of specimens. The data support the view that R. robustus represents a species complex. Levels of sequence divergence between clades within each region are compatible with a Pleistocene origin. Nucleotide diversity (π) for all R. prolixus populations was extremely low (0.0008), suggesting that this species went through a recent bottleneck, and was subsequently dispersed by man.

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

Lack of pharmacokinetic interaction between ropinirole and theophylline in patients with Parkinson's disease - C. Thalamas; A. Taylor; C. Brefel-Courbon; S. Eagle; K. Fitzpatrick; O. Rascol (European Journal of Clinical Pharmacology, 1999)

In Vitro Earthworm Lumbricus terrestris Coelomocyte Assay for Use in Terrestrial Toxicity Identification Evaluation - S. W. Burch; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman (Bulletin of Environmental Contamination and Toxicology, 1999)

Wound Healing in Earthworms Lumbricus terrestris: A Cellular-Based Biomarker for Assessing Sublethal Chemical Toxicity - M. A. Cikutovic; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman; E. L. Cooper (Bulletin of Environmental Contamination and Toxicology, 1999)

Estimation of habituation and signal-to-noise ratio of cortical evoked potentials to oesophageal electrical and mechanical stimulation - M. V. Kamath; G. Tougas; S. Hollerbach; R. Premji; D. Fitzpatrick; G. Shine; A. R. M. Upton (Medical & Biological Engineering & Computing, 1997)

Equine herpesvirus genomes: Heterogeneity of naturally occurring type 4 isolates and of a type 1 isolate after heterologous cell passage - M. J. Studdert; D. R. Fitzpatrick; G. F. Browning; A. A. Cullinane; J. M. Whalley (Archives of Virology, 1986)

Potato glycoalkaloids: Increases and variations of ratios in aged slices over prolonged storage - T. J. Fitzpatrick; S. F. Herb; S. F. Osman; J. A. McDermott (American Journal of Potato Research, 1977)

Chemical composition of potatoes. VIII. Effect of variety, location, and year of growth on the content of nitrogen compounds - Eugene A. Talley; Thomas J. Fitzpatrick; William L. Porter (American Journal of Potato Research, 1970)

Chemical composition of potatoes. IV. Relationship of the free amino acid concentrations to specific gravity and storage time - Eugene A. Talley; Thomas J. Fitzpatrick; William L. Porter (American Journal of Potato Research, 1964)

Studies of the relationship of specific gravity to total solids of potatoes - W. L. Porter; T. J. Fitzpatrick; E. A. Talley (American Journal of Potato Research, 1964)

Chemical composition of potatoes. III. Relationships between specific gravity and the nitrogenous constituents - Thomas J. Fitzpatrick; Eugene A. Talley; William L. Porter; Hugh J. Murphy (American Journal of Potato Research, 1964)

Trends in potato production and sales, 1940–1950 - Robert A. Fitzpatrick (American Journal of Potato Research, 1953)